2019
DOI: 10.1371/journal.pone.0216496
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis of silver nanoparticles via Cynara scolymus leaf extracts: The characterization, anticancer potential with photodynamic therapy in MCF7 cells

Abstract: In this study, we report on the synthesis of silver nanoparticles (AgNPs) from the leaf extracts of Cynara scolymus (Artichoke) using microwave irradiation and the evaluation of its anti-cancer potential with photodynamic therapy (PDT). Silver nanoparticles formation was characterized by scanning electron microscopy with energy dispersive x-ray spectroscopy and Fourier transform infrared (FTIR) spectroscopy. Silver nanoparticles formation was also investigated the surface charge, particl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
98
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 229 publications
(132 citation statements)
references
References 53 publications
9
98
1
1
Order By: Relevance
“…Induction of cytotoxicity of nanoparticles depends not only on their shape, surface chemistry, or size but also on the cell line studied. Erdogan et al, 21 reported that green silver nanoparticles induced toxicity and showed anti-cancer effects with phototherapy in MCF7 cells.…”
Section: Introductionmentioning
confidence: 99%
“…Induction of cytotoxicity of nanoparticles depends not only on their shape, surface chemistry, or size but also on the cell line studied. Erdogan et al, 21 reported that green silver nanoparticles induced toxicity and showed anti-cancer effects with phototherapy in MCF7 cells.…”
Section: Introductionmentioning
confidence: 99%
“…In order to determine the cells levels of caspase-3 activity, cells were lysed with cell lysis buffer and centrifuged for 10 min at 9000 rpm at 4˚C after treatment of Anti-miR-144 (20 nM) for 36 h (Erdogan et al, 2019). Using a commercial kit (Calbiochem, USA) and following the manufacturer's instructions, the supernatant was used for measuring caspase-3 activity as a marker of apoptosis in cells.…”
Section: Caspase-3 Activity Assaymentioning
confidence: 99%
“…An organic methodology has been utilized in the synthesis of AgNPs utilizing microorganisms, fungi and plant extract prompting to reliable alterative to chemical and physical techniques in acquiring the nanoparticles in controlled particle size. It has been seen that green synthesis of AgNPs with various stabilizing agents, for example, polyethylene glycol, alcohol vinyl, dextran, cyclodextrins and utilizing DOI: http://dx.doi.org/10.5772/intechopen.90717 "andeli" (rose extract) [19][20][21][22]. This expands utilization of AgNPs in different materials has prompted a more straightforward and direct exposure in human and raised potential dangers to health issues.…”
Section: Toxicity Of Silver Nanoparticlesmentioning
confidence: 99%